2020
DOI: 10.1186/s12978-020-0853-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of obstetric danger signs and associated factors: a study among mothers in Shashamane town, Oromia region, Ethiopia

Abstract: Background: Child birth which is a special moment for parents, families and communities is also a time of intense vulnerability. In many developing countries including Ethiopia, maternal morbidity and mortality still pose a substantial burden. Raising awareness of women about the danger signs of pregnancy and childbirth is the first essential step in appropriate and timely obstetric care. Objective: To assess the knowledge of obstetric danger signs among mothers and associated factors in Shashamane town, oromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 10 publications
8
66
4
1
Order By: Relevance
“…This difference might be due to socio-cultural difference and difference of sample size used. This study is higher than study conducted in Shashemane stated that (64.7%) [18].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This difference might be due to socio-cultural difference and difference of sample size used. This study is higher than study conducted in Shashemane stated that (64.7%) [18].…”
Section: Discussioncontrasting
confidence: 68%
“…The cross section study conducted in Kenya stated that the mother included under study only (4.7%) know about Obstetric danger which was Vaginal bleeding and the same study conducted in Uganada stated that (52%) as well as study conducted in Ethiopia in Adama city stated 44% and the same study conducted Ethiopia in Dire Dawa stated 24.4 knew about Obstetric danger signs, it's low when compare to this study [16,[18][19][20][21]. It due to educational status and Age of the mothers during that time.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, respondents who had more antenatal visits were more knowledgeable than those who had less number and this is consistent with other studies. (28,29) Antenatal care provides an opportunity to counsel pregnant women about serious ODS during pregnancy. However, Mwilike et al, 2018 found that there was not any statistically significant association between women's knowledge of danger signs during pregnancy and the number of antenatal visits.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is in line with the previous variable, parity. Better knowledge of the danger signs of pregnancy makes pregnant women more aware and better prepared for labor [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%